Adicción al internet y su relación con los hábitos de sueño, alimentación y ejercicio físico de los alumnos del bachillerato del colegio de Bachillerato Macará durante el periodo marzo-julio 2014 - Ramírez Cueva, María José (2015)
Since its inception, Internet has taken a turn in the life most of the population. Being teenagers the group greater Access have to this service, the uncontrolled and excessive use can carry to what is commonly referred to as Internet addiction and cause changes in life styles, as well as the family and social environment. This investigative work is attempted to a quantitative, descriptive cross sectional study, whose main objective was to determine the Internet addiction in Bachelor of secondary school students “Macará” and the relationship that exists with sleep, food and exercise habits. The simple was composed of 139 students in secondary education from 16 to 21 years of age who answered a survey with questions related to the habits of sleep, food and physical exercise; and the Young Internet addiction test. The statistical analysis was performed using the program Excel 2013, then the results is tables and charts (bars and cakes), obtaining the following resulted: 17,99 % simple shows Internet addiction, predominantly male, and the aged between 14 and 16 years. To revise the hours of sleep the highest percentage of internet addicted population sleeps from 2 to 4 hours a day, same meals is 3 to 5 days, being fast food favorite and most consumed by this group of teenagers, and finally the highest percentage devoted hours to exercise. Key words: addiction, internet, sleep, exercise, food, students.